ANALYSIS OF POSSIBLE COMPLICATIONS AFTER CHEMICAL TEETH WHITENING - Токмакова, Светлана Ивановна; Побединская, Людмила Юрьевна; Бондаренко, Ольга Владимировна; Луницына, Юлия Васильевна; Бекжанова, Ольга Есеновна; Мокренко, Евгений Владимирович (Medicine in Kuzbass, 2024)
Chemical teeth whitening is becoming an increasingly requested and popular procedure every year, and manufacturers are steadily expanding the range of whitening systems. Many doctors and patients do not have a full understanding and their own point of view about the existing risks of tooth color correction and the expediency of such procedures. Therefore, research in this direction remains relevant today.The purpose of the study is to identify and analyze the likely complications that occur after the procedure of chemical teeth whitening.Materials and methods. With the help of the developed questionnaire, anonymous interviews of patients on awareness issues regarding chemical teeth whitening were conducted. Statistical processing was carried out.Results. According to the results of the patient survey, it was revealed that the teeth whitening service is becoming increasingly popular among the population, however, a significant proportion of respondents have very superficial knowledge about its safety and side effects, as well as ways to prevent complications. Among those who have had experience with teeth whitening, the percentage of people who performed this procedure independently at home is high, which inevitably increases the risk of side effects. At the same time, the respondents most often observed an increased sensitivity of their teeth to various stimuli after the procedure.Conclusion. The results obtained indicate the increasing interest of patients in the procedure of chemical teeth whitening, which is associated with the desire to have a snow-white smile. At the same time, the survey data showed some limitations of both the population and some dentists in matters related to the safety of this procedure.
Keywords: chemical teeth whitening; questionnaires; dental hyperesthesia; complications after teeth whitening